Effect of bank internal control system on non-financial performance of selected quoted deposit money bank in Nigeria - Nwobodo, Helen; Adegbie, Fola. F.; Banmore, O. O. (Journal of Management, Economics, and Industrial Organization, 2020)
The increasing trend of declined in bank efficiency and operational performance in recent years raised unquestionable concerned and pose serious threats to the stability and survival of deposit money banks across the globe. Studies have shown that most deposit money banks in Nigeria have experienced declined in bank efficiency and operational performance due to weak internal control system thus caused financial losses to banks and loss of public confidence in the banking sector. The study employed a survey research design and the population was 568 staff and the sample size used was 292 using Cochran sample size determination. The reliability coefficient ranged from 0.71 to 0.94. The study found out that internal control system has positive and significant effect on bank efficiency and operational performance of the selected quoted deposit money banks with (P
Keywords: bank operational performance; bank efficiency; deposit money bank; internal control